(untitled) (Bioagro, 2025)
The use of biostimulants has been an agricultural strategy to improve crop yield and quality. These products can be a sustainable alternative that aligns with ecological agricultural practices, promoting increased productivity and minimising environmental impact. The study consisted of evaluating the effect of biostimulants on rice crop development and yield. A randomised complete block design was used with a factorial arrangement of three biostimulants by three doses plus a control treatment. The variables evaluated were plant height, number of tillers per plant, number of days to flowering, number of grains per ear, weight of 1000 grains and yield. The results show that the biostimulants stimulated the growth and yield of the rice crop. The variables plant height and number of tillers were benefited with the treatments T3 (Isabión, 1000 mL·ha-1) followed by T9 (Proboost, 1000 mL·ha-1); the same treatments promoted an increase in the number of grains per spike and weight of 1000 grains. Treatment T3 showed the highest yield with a value of 4472.19 kg·ha-1. The application of the biostimulant Isabión at a dose of 1000 mL·ha-1 showed the best results in the variables evaluated.